Recognizability and the Application of Quality Labels and Authenticity in Everyday Use - Borec, Andreja; Zdrilić, Ivica; Prpić, Ana Marija; Ivanov, Kristina; Surać, Lucija (Oeconomica Jadertina, 2017)
The process of globalization had a large impact on the market of agricultural and food products by making it saturated with new products that compete with each other in price and quality. In such global circumstances, the indigenous products cannot cope with the fierce competition, and the buyers cannot be sure of the quality of what they are buying, resulting in the need to protect indigenous products. The aim of this paper is to point out the importance of creating a label and its protection as an intellectual property. The paper identifies and displays the marks of authenticity and quality in the Republic of Croatia and on the territory of the European Union, and it provides Croatian examples of origin protection. For the purpose of this work and in relation to the recognition of quality and authenticity in everyday use a survey was conducted among sixty-eight respondents who chose to make their purchases within a retail chains, thirty one respondents who chose a family farm based market, and twenty-two which chose small family farms. Research has shown that there are differences between individual age groups and their preferences when purchasing at retail chains or from family farm based markets. In addition, customers focus on the quality and price when purchasing products, but they inadequately recognize the quality of products by observing markings of origin and of quality.